Artistic Interpretation Of Events In Nadira Poetry - Eshonkulova Surayyo Isomiddinovna (International Scientific and Current Research Conferences, 2021)
This tezis is devoted to an analysis of the artistic depiction of life events in Nodira's poetry; to transmission of her philosophical views to further generations on how a kind ruler, a true beloved, loving father, perfect man should be, through creating the image of his fiance Umarkhan.